Towards a Typology of Surprise in Organ Music - Zubova, Nadezhda (situArte, 2024)
The current article is dedicated to the emotion of surprise in music. It is a part of a wider research on the musical surprise and its role in the aesthetical perception. The main aim of this work is to explore the origins of musical surprise with the purpose of developing a typology of this emotion in organ music. Based on the analysis of harmony, melody, rhythm, and dynamics of some musical compositions, an attempt is made to distinguish the features of the musical text that contribute to the arousal of the emotion of surprise. Furthermore, we inquire into the emotion of surprise induced in the studied cases and conclude that there exist three types of musical surprise.